Reliability modeling and analysis of environmental control and life support systems of space stations: A literature survey. (February 2019) - Sharma, Garima; Rai, Rajiv Nandan
Abstract: Ultra reliable life support is needed for environmental control and life support systems (ECLSS) of space stations (SS) because provisioning of spare parts or a speedy crew recovery may not be a feasible option. There is limited work on the reliability modeling and analysis (RMA) of ECLSS of a SS. In addition, presently the literature review on RMA of space stations which is the central theme of the paper is not organized in a formalized manner and the ideas presented are spread out and limited in developing a consolidated literature review in a sequential manner. The paper presents a detailed literature survey on the RMA of SS ECLSS. The paper also highlights the research gaps and an overview of latest RMA models that can be applied for the reliability analysis of SS ECLSS. The paper contributes by providing sufficient insights into the complete development of RMA of the SS ECLSS comprehensively for better understanding of the readers. Highlights: Literature review papers on the subject are limited in the literature. The paper presents a consolidated literature review in a sequential manner. Review on reliability basic, prediction, estimation and optimization models. Research gaps and an overview of latest reliability analysis models are covered. The paper provides due insights into the subject for better understanding.